Emerging T cell immunoregulatory mechanisms in multiple sclerosis and Alzheimer’s disease - Hawiger, Daniel (Frontiers in Aging Neuroscience, 2024)
Multiple sclerosis (MS) and Alzheimer’s disease (AD) are neuroinflammatory and neurodegenerative diseases with considerable socioeconomic impacts but without definitive treatments. AD and MS have multifactorial pathogenesis resulting in complex cognitive and neurologic symptoms and growing evidence also indicates key functions of specific immune cells. Whereas relevant processes dependent on T cells have been elucidated in both AD and MS, mechanisms that can control such immune responses still remain elusive. Here, a brief overview of select recent findings clarifying immunomodulatory mechanisms specifically induced by tolerogenic dendritic cells to limit the activation and functions of neurodegenerative T cells is presented. These insights could become a foundation for new cutting-edge research as well as therapeutic strategies.